Immunization of mice with recombinant mosquito salivary protein D7 enhances mortality from subsequent West Nile virus infection via mosquito bite. - Krystle L Reagan; Carlos Machain-Williams; Tian Wang; Carol D Blair (Public Library of Science (PLoS), 2012)
Mosquito salivary proteins (MSPs) modulate the host immune response, leading to enhancement of arboviral infections. Identification of proteins in saliva responsible for immunomodulation and counteracting their effects on host immune response is a potential strategy to protect against arboviral disease. We selected a member of the D7 protein family, which are among the most abundant and immunogenic in mosquito saliva, as a vaccine candidate with the aim of neutralizing effects on the mammalian immune response normally elicited by mosquito saliva components during arbovirus transmission.We identified D7 salivary proteins of Culex tarsalis, a West Nile virus (WNV) vector in North America, and expressed 36 kDa recombinant D7 (rD7) protein for use as a vaccine. Vaccinated mice exhibited enhanced interferon-γ and decreased interleukin-10 expression after uninfected mosquito bite; however, we found unexpectedly that rD7 vaccination resulted in enhanced pathogenesis from mosquito-transmitted WNV infection. Passive transfer of vaccinated mice sera to naïve mice also resulted in increased mortality rates from subsequent mosquito-transmitted WNV infection, implicating the humoral immune response to the vaccine in enhancement of viral pathogenesis. Vaccinated mice showed decreases in interferon-γ and increases in splenocytes producing the regulatory cytokine IL-10 after WNV infection by mosquito bite.Vector saliva vaccines have successfully protected against other blood-feeding arthropod-transmitted diseases. Nevertheless, the rD7 salivary protein vaccine was not a good candidate for protection against WNV disease since immunized mice infected via an infected mosquito bite exhibited enhanced mortality. Selection of salivary protein vaccines on the bases of abundance and immunogenicity does not predict efficacy.